Reversal of Chronic Hypoperfusion to Improve Cognitive Function: The RECON Trial - Nichols, Emma Hitt (MD Conference Express, 2013)
Carotid artery disease is thought to be one of the causes of cognitive dysfunction, but treatment of the associated cerebral blood flow impairment has never been tested in a randomized controlled trial [Marshall RS et al. Neurology 2012], according to the results of the Randomized Evaluation of Carotid Occlusion and Neurocognition trial [RECON; NCT00390481].